Economic evaluation of the use of exogenous pulmonary surfactants in preterm newborns in a Mexican population Evaluación económica de la utilización de surfactantes pulmonares exógenos en recién nacidos pretérmino en población mexicana - Guillermo Salinas-Escudero; Alfonso Reyes-López; Juan Garduño-Espinosa; Miguel Angel Villasís-Keever; Silvia Martínez-Valverde; Onofre Muñoz-Hernández (Instituto Nacional de Salud Pública, 2012)
OBJECTIVE: To estimate the cost-effectiveness ratio of surfactant rescue treatment of premature infants with respiratory distress syndrome (RDS) who are covered by the Medical Insurance for a New Generation. MATERIALS AND METHODS: A cost-effectiveness evaluation was conducted from the third-payer perspective. Comparisons were made between the use of bovine surfactant (BS) therapy and without BS therapy. A decision tree model with a lifetime horizon was used where the measurements of effectiveness were life years gained (LYG) and quality-adjusted life years (QALYs). A 5% discount rate was considered for costs and health outcomes. All costs are expressed in Mexican pesos 2009. RESULTS: Incremental cost-effectiveness ratios (ICER) were MXN$136670 per LYG and MXN$125250 per QALY. CONCLUSION: Surfactant therapy was confirmed as a cost-effective strategy in accordance with World Health Organization criteria of three per capita gross domestic product (GDP) per QALY in premature infants with RDS in Mexico. OBJETIVO: Estimar la razón de costo efectividad incremental del tratamiento de surfactante de rescate en pacientes pretérmino con Síndrome de Dificultad Respiratoria (SDR) cubiertos por el Seguro Médico para una Nueva Generación. MATERIAL Y MÉTODOS: Evaluación de costo-efectividad desde la perspectiva del tercer pagador. Los comparadores fueron la terapia de surfactante bovino y la alternativa de no emplear ésta. Se utilizó un árbol de decisión que consideró la esperanza de vida como horizonte temporal y las medidas de efectividad fueron los años de vida ganados (AVG) y los años de vida ajustados por calidad de vida ( AVAC).Resultados en pesos mexicanos del 2009. RESULTADOS: Las RCEI por AVG y AVAC fueron de MXN$136670 y MXN$125250. CONCLUSIÓN: La razón de costo por AVG y AVAC para la terapia de surfactantes en pacientes prematuros con SDR en México fue menor a tres veces el PIB per cápita, por lo que es una estrategia costo-efectiva según los criterios de la OMS.